PENGAMBIL KEPUTUSAN DALAM KELAS BAHASA INGGRIS SEBAGAI BAHASA ASING: STUDI KASUS MENGENAI PERAN GURU YANG TERSEMBUNYI - Kardena, Absharini (Universitas Mahaputra Muhammad Yamin, 2024)
In the EFL classroom, teachers have some roles that directly influence students’ achievement. One of the main roles is being a decision-maker during teaching and learning processes, which including planning, implementing and evaluation. During the implementation of Independence curriculum, as the newest curriculum, the teachers are positioned as one of the important factors in succeeding the curriculum by actively doing their role as a decision maker. Thus, the decisions taken by English teachers might influence the teaching and learning processes. This article aims to discuss how English teachers play their role as decision-makers in conducting English subjects at school, specifically on deciding learning goals, teaching materials, teaching activity and learning evaluation. This research, which is derived and further developed based on previous research conducted in 2013, was conducted at one of the Public Islamic Senior High Schools in Solok City, West Sumatera, Indonesia. Furthermore, this research involved 5 English teachers. The research was conducted under a qualitative approach by using a phenomenology design. The result of the research shows that most English teachers did not actively decide their teaching and learning process, especially on learning evaluation. It was caused by a lack of understanding about the importance of decisions made by the teachers; the decisions they made may influence the whole process of teaching English. Besides, it is also influenced by an external factor, such as the government’s rule. Meanwhile, the research also found that the role of a decisions maker can either influence or even is influenced by the other roles of English teacher. The result of the research show a current need for the teachers to get trainings that may help them to enhance their performance as a decision maker in the classroom.